VALUE CHAINS ANALYSIS OF ORGANIC VEGETABLES (Case Study at Mulyo Santoso Farmers Group in Sukun Subdistrict of Malang City) - Harmawati Haddas (Agricultural Socio-Economics Journal, 2018)
ABSTRACT: Increased income and healthy lifestyle trend encourage people to switch to consuming non-organic food products to organic food products. This encourages producers in developing organic vegetable business. This research was conducted for the development of organic vegetable business by using value chain analysis. Respondent determination was done by census as many as 30 farmers of organic farming at MulyoSantoso Farmer Group in Malang City, and the determination of merchant respondents using snowball sampling. The results show that farmers earn the smallest margin compared to other actors this is because the price received by farmers is determined by the trader. Organic vegetable marketing channel there are four kinds of channels, where farmers who can sell directly to consumers will get the highest profit. This is also related to the efforts of farmers in increasing the added value in processing vegetables into chips and sauces, where farmers are able to increase added value then the profits are also increased. The results of Benchmarking and Upgrading indicate that increasing the added value and capability of farmers to increase production capacity and harvesting the utilization of technology needed to reduce losses post-harvest.